DEVELOPMENT OF WEBSITE-BASED LEARNING MEDIA FOR ENGINEERING DRAWING SUBJECTS AT NATIONAL VOCATIONAL SCHOOL MALANG - Aditya Bagus Putra Sangrila; Marsono (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The rapid development of information technology has encouraged the need for innovative learning media to improve the quality of Technical Drawing instruction in vocational high schools. Learning activities that are still dominated by conventional teaching methods often result in students being less actively engaged and experiencing difficulties in understanding the learning materials. This study aimed to develop a website-based learning medium for the Technical Drawing subject at SMK Nasional Malang and to determine its validity, practicality, and feasibility. The study employed the Research and Development (R&D) method using Arief S. Sadiman's development model, which consists of needs identification, objective formulation, material development, assessment instrument development, media script writing, media production, validation, revision, and product testing. The product was validated by a media expert and a subject-matter expert. The field testing involved two Technical Drawing teachers, 10 students in a small-group trial, and 35 eleventh-grade students from the Mechanical Engineering program at SMK Nasional Malang. Data were collected using questionnaires and analyzed descriptively using percentage analysis. The results showed that both the media expert and subject-matter expert validation achieved a score of 95%, while the teacher trial obtained 96.25% and student responses reached 84.31%, all of which were categorized as highly valid. Therefore, the developed website-based learning medium is considered highly valid, practical, and feasible for use in Technical Drawing instruction at SMK Nasional Malang .